Pengaruh Faktor Budaya, Sosial, Pribadi, dan Psikologis Terhadap Keputusan Pembelian Produk Sambal Kaisar di Kota Pontianak - Nuriska Sepsi; Eva Dolorosa; Dewi Kurniati (KOLONI, 2026)
This study aims to analyze the influence of cultural, social, personal, and psychological factors on the purchase decisions of Sambal Kaisar products in Pontianak City and to examine the moderating role of brand image. A quantitative approach with descriptive and associative research designs was employed. Data were collected through questionnaires distributed to 100 Sambal Kaisar consumers selected using purposive sampling. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The findings indicate that cultural and social factors have a positive and significant effect on purchase decisions, with the social factor emerging as the most dominant determinant. In contrast, personal and psychological factors do not significantly influence purchase decisions. Brand image also has no significant direct effect on purchase decisions and fails to moderate the relationships between cultural, social, personal, and psychological factors and purchase decisions. The structural model demonstrates satisfactory explanatory power, with an R² value of 0.736, indicating that 73.6% of the variance in purchase decisions is explained by the proposed variables, while the Q² value of 0.408 confirms good predictive relevance. These findings suggest that consumers' purchase decisions toward Sambal Kaisar are primarily driven by cultural consumption habits and social influences rather than personal characteristics, psychological considerations, or brand image.